Quiet Quitting Among Millennials: Causing Factors And Its Impact On Employees' Performance In The Public And Private Sectors - Agustinah, Agustinah; Susena, Karona Cahya; Kresnawati, Kresnawati (UNIVED Press, 2026)
The phenomenon of quiet quitting is increasingly observed among millennial employees, driven by shifting values, expectations, and the pursuit of work-life balance. This study analyzes the determinants of quiet quitting, its impact on the performance of millennial employees in the government and private sectors in Bengkulu Province, and compares the two sectors. Using a quantitative approach, questionnaires were distributed to 250 non-managerial employees, and data were analyzed using PLS-SEM and Multi-Group Analysis (MGA). All measurement instruments met validity and reliability criteria. The findings show that job demands significantly reduce employee engagement and increase quiet quitting, while job resources significantly enhance engagement and performance but do not directly influence quiet quitting. Employee engagement was found to improve performance and reduce quiet quitting, whereas quiet quitting negatively affected performance. A significant chain mediation effect was identified through employee engagement and quiet quitting in the relationship between job demands, job resources, and performance. MGA results indicated no significant differences between the government and private sectors. The study highlights the importance of managing job demands and strengthening job resources through proactive HR practices, Leadership support, balanced workloads, and career development to minimize quiet quitting and sustain organizational performance.